The Legal Protection of Ngajat Lesung Dance as a Copyright for Traditional Cultural Expressions - Karlina, Dina (JURNAL USM LAW REVIEW, 2023)
Traditional art must be protected as it is included in Intellectual Property Rights (IPR), including Copyrights. The Copyright law aims to protect works of art created by artists. In addition, it can facilitate individual creativity or expression for the broad benefit of humanity, ensuring that the rights to property owned by artists are recognized, respected and can be defended on actions that violate their rights. Ngajat Lesung dance is a traditional dance that belongs to the Village of Sejuang, Seluar District, Bengkayang Regency. The empirical legal approach is the method for conducting this research. This method involved by directly collecting predetermined data and information. The collected results were then collected and analyzed to determine how the implementation of Legal Protection for Ngajat Lesung dance as a Copyright of Traditional Cultural Expressions in Seluas District, Bengkayang Regency. Copyright Legal Protection for Ngajat Lesung dance has yet to be carried out optimally by the Regional Government of Bengkayang Regency through the Department of Youth, Sports, and Tourism. This is because the efforts made by the Regional Government have not been maximized to educate artists regarding the protection of Copyright law for traditional culture, causing the artist's ignorance of the importance of protection for the work that has been made. In addition, the artist thinks that registering the Copyright for Traditional Dances requires a large fee and is very expensive. Therefore, the Regional Government of Bengkayang Regency through the Youth, Sports, and Tourism Service, is expected to pay more attention and educate to help the artists inventory and register Ngajat Lesung Dance. This dance is part of various Traditional Cultural Expressions in the field of Intellectual Property. Registering the Copyright of Ngajat Lesung Dance and having it listed as a Traditional Cultural Art with the Directorate General of Intellectual Property is important.